Structural and Functional Trajectories of Middle Temporal Gyrus Sub-Regions During Life Span: A Potential Biomarker of Brain Development and Aging - Xu, Jinping; Zhang, Jinhuan; Li, Jiaying; Wang, Haoyu; Chen, Jianxiang; Lyu, Hanqing; Hu, Qingmao (Frontiers in Aging Neuroscience, 2022)
Although previous studies identified a similar topography pattern of structural and functional delineations in human middle temporal gyrus (MTG) using healthy adults, trajectories of MTG sub-regions across lifespan remains largely unknown. Herein, we examined gray matter volume (GMV) and resting-state functional connectivity (RSFC) using dataset from Nathan Kline Institute (NKI), and aimed to (1) investigate structural and functional trajectories of MTG sub-regions across lifespan; and (2) assess whether these features can be used as biomarkers to predict individual’s chronological age. As a result, GMV of all MTG sub-regions followed U-shaped trajectories with peak ages around sixth decade. The RSFC between MTG sub-regions and many cortical brain regions showed inversed U-shaped trajectories, whereas showed U-shaped way for sub-cortical regions/cerebellum, with peak ages about twenty years earlier than those of GMV. Moreover, GMV and RSFC of MTG sub-regions could be served as useful features to predict individual age with high estimation accuracy. Together, these results not only provided novel insights into dynamic process of structural and functional roles of MTG sub-regions across lifespan, but also served as useful biomarkers to age prediction.